A Simple Colorimetric Assay for Sensitive Cu2+ Detection Based on the Glutathione-Mediated Etching of MnO2 Nanosheets - Tang, Shurong; Liu, Qiao; Hu, Jie; Chen, Wei; An, Fengping; Xu, Hui; Song, Hongbo; Wang, Yi-Wei (Frontiers in Chemistry, 2021)
In this paper, we developed a quick, economical and sensitive colorimetric strategy for copper ions (Cu2+) quantification via the redox response of MnO2 nanosheets with glutathione (GSH). This reaction consumed MnO2 nanosheets, which acted as a catalyst for the oxidation of 3,3',5,5'-tetramethylbenzidine (TMB) to a blue product (oxTMB). In the presence of Cu2+, the GSH was catalyzed to GSSG (oxidized glutathione), and the solution changed from colorless to deep blue. Under the optimum conditions, the absorption signal of the oxidized product (oxTMB) became proportional to Cu2+ concentration in the range from 10 to 300 nM with a detection limit of 6.9 nM. This detection system showed high specificity for Cu2+. Moreover, the system has been efficaciously implemented for Cu2+ detection in actual tap water samples. The layered-nanostructures of MnO2 nanosheets make it possess high chemical and thermal stability. TMB can be quickly oxidized within 10 min by the catalyzing of MnO2 nanosheets with high oxidase-like activity. There is no need of expensive reagents, additional H2O2 and complicated modification processes during the colorimetric assay. Therefore, the strategy primarily based on MnO2 nanosheets is promising for real-time, rapid and highly sensitive detection of Cu2+ under practical conditions.